Response of Date Palm (Phoenix dactylifera L.) to Environmental Stresses: A Review Article - Al-Hamoud, Firas M.; Mahdi, Ali S.; Al-Darwish, Mohammed A. (Basrah Journal Of Date Palm Research, 2025)
The aim of the present review is to summarize the latest scientific studies addressing the responses of date palm (Phoenix dactylifera L.) to environmental stresses, with a particular focus on drought, heat, and salinity stresses, especially in the context of current global climate changes. These stresses represent major factors affecting the growth and productivity of date palms. Such conditions induce a range of morphological, physiological, biochemical, anatomical, and molecular changes that constitute the tree’s adaptive responses to unfavorable environments. The results indicate that date palm possesses a high degree of adaptability, enabling it to maintain essential vital functions under harsh environmental conditions. Its responses include adjustments in photosynthesis, water and ion balance, osmotic regulation, as well as metabolic reprogramming and activation of antioxidant systems. Molecular and proteomic analyses reveal precise gene regulation and flexible gene expression, reflecting the ability of date palm to modulate critical cellular processes and adapt to multiple stresses. Genetic variation among cultivars further demonstrates differing potentials for stress tolerance. This review highlights a comprehensive understanding of date palm responses to multiple environmental stresses, providing a solid scientific foundation for developing effective strategies to enhance the resilience of this crop and ensure sustainable production under global climate change.